Total synthesis of the potent anti-inflammatory natural product solomonamide A along with structural revision and biological activity evaluation - Jachak, Gorakhnath R.; Athawale, Paresh R.; Agarwal, Heena; Barthwal, Manoj Kumar; Lauro, Gianluigi; Bifulco, Giuseppe; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2018)
Herein, we report the total synthesis of solomonamide A along with its structural revision for the first time. The natural product possesses very potent anti-inflammatory activity, and it contains a macrocyclic peptide having four consecutive stereocenters on an unnatural amino acid component. The key features in the present synthesis include the application of an Evans aldol reaction, ligand-free Heck macrocyclization and chemoselective oxidations. The challenging task of fixing the stereochemistry of OH at the C5-position was accomplished with the help of DFT calculations, applying a quantum-mechanical (QM)/NMR combined approach. Biological evaluation in a mouse paw edema model revealed that a low dose (0.3 mg kg(-1)) of the synthesized solomonamide A showed 74% reduction at 6 h, which was comparable to a high dose (10 mg kg(-1)) standard drug dexamethasone effect (75% at 6 h). Thus, we further confirmed the revised structure of solomonamide A.

Comprehensive study on solomonamides: total synthesis, stereochemical revision, and SAR studies toward identification of simplified lead - Jachak, Gorakhnath R.; Kashinath, K.; Vasudevan, N.; Athawale, Paresh R.; Choudhury, Rahul; Dange, Santoshkumar S.; Agarwal, Heena; Barthwal, Manoj Kumar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
Solomonamides, a pair of macrocyclic peptide natural products originating from marine sources, have garnered significant attention within the synthetic community owing to their marked anti-inflammatory efficacy and intricate molecular architectures. In this paper, we present a very detailed investigation into solomonamides, including the challenges associated with the total synthesis, the evolution of our synthetic strategies, structural reassignment, synthesis of all possible stereoisomeric macrocycles, biological assessment, structure-activity relationship (SAR) studies, etc. Within the ambit of this total synthesis, diverse strategies for macrocyclization were rigorously explored, encompassing the Friedel-Crafts acylation, cyclization involving the aniline NH2 moiety, macrolactamization utilizing Gly-NH2, and Heck macrocyclization methodologies. In addition, an array of intriguing chemical transformations were devised, including but not limited to photo-Fries rearrangement, Wacker oxidation, ligand-free Heck macrocyclization, oxidative cleavage of indole, synthesis of contiguous stereocenters via substrate/reagent-controlled protocols, and simultaneous making and breaking of olefinic moieties. The findings of this investigation revealed a structurally simplified lead compound. Remarkably, the lead compound, while possessing structural simplification in comparison to the intricate solomonamide counterparts, demonstrates equipotent in vivo anti-inflammatory efficacy.